2010
DOI: 10.1111/j.1399-3062.2010.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin infections in Egyptian renal transplant recipients

Abstract: Our RTRs have higher prevalence rates of folliculitis and superficial fungal infections than the healthy population and they should be searched for in every patient with renal transplantation to ensure early treatment and avoid complications. Low-dose ketoconazole should be considered in renal transplant populations with high rates of superficial fungal infections, as it may reduce risk of such infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The available literature indicates that the incidence of viral warts is varied from 11% to 53% of the population of patients after transplantation. 16,17 In our study, its appearance was observed in 38.5% of the patients, which is similar to the results obtained by Ramsay et al (42%). 17 We observed a correlation between the age of the patients after kidney transplantation, and the presence of viral warts on the feet (patients with warts were much older), and the same observation was made by Pruvost et al 18 The number of warts increases with the duration of immunosuppressive therapy, which is consistent with the observations of other authors.…”
Section: Methodssupporting
confidence: 82%
“…The available literature indicates that the incidence of viral warts is varied from 11% to 53% of the population of patients after transplantation. 16,17 In our study, its appearance was observed in 38.5% of the patients, which is similar to the results obtained by Ramsay et al (42%). 17 We observed a correlation between the age of the patients after kidney transplantation, and the presence of viral warts on the feet (patients with warts were much older), and the same observation was made by Pruvost et al 18 The number of warts increases with the duration of immunosuppressive therapy, which is consistent with the observations of other authors.…”
Section: Methodssupporting
confidence: 82%
“…In contrast, OM was more prevalent in those KTR without diabetes, suggesting that KTR per se was the predisposing condition: 25% of our non-diabetic KTR patients had OM. A single study addressed the role of diabetes in fungal skin infections in KTR, reporting increased prevalence in diabetic KTR [15] ; unfortunately, the analysis included OM and dermatophytosis altogether, the latter corresponding to most (72%) of the diagnoses. The reason for diabetes being a risk factor of OM in HD patients, but a "protective" factor in KTR is intriguing and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons may account for this variation, including different socio-demographic characteristics among the cohorts studied (e.g., gender and age), and different diagnostic criteria, often not clearly defined. In addition, only few studies compared the prevalence of OM with a control group, usually recruited among hospital staff [7,9,11,15] . Of note, there are no reports on the effectiveness of the current treatments for OM in these groups of patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Onychomycosis is associated with patient dissatisfaction and decreased quality of life [8,9]. It is a common comorbidity of advanced age [10], diabetes [11,12], peripheral vascular disease [13], HIV [14], immunosuppression [15], obesity [16] and smoking [13]. …”
Section: Introductionmentioning
confidence: 99%